2010
DOI: 10.1007/s10658-010-9728-4
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrocarpon species associated with apple tree roots in South Africa and their quantification using real-time PCR

Abstract: Cylindrocarpon species are known to be a component of the pathogen/pest complex that incites apple replant disease. In South Africa, no information is available on apple associated Cylindrocarpon species and their pathogenicity. Therefore, these aspects were investigated. Among the isolates recovered from apple roots in South Africa, four species (C. destructans, C. liriodendri, C. macrodidymum and C. pauciseptatum) were identified using β-tubulin gene sequencing and phylogenetic analysis. This is the first re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 29 publications
1
66
0
1
Order By: Relevance
“…Cylindrocarpon and Cylindrocarpon-like species have since been commonly associated with root and decay of woody and herbaceous plants (Domsch et al 2007). Cylindrocarpon root rot causes losses up to 30% on ginseng (Panax quinquefolium) (Seifert et al 2003), and plays an important role in black foot rot of grapevines (Halleen et al 2004(Halleen et al , 2006, apple replant disease (Tewoldemedhin et al 2010), and beech cankers (Castlebury et al 2006), to name but a few hosts of economic importance.…”
Section: Introductionmentioning
confidence: 99%
“…Cylindrocarpon and Cylindrocarpon-like species have since been commonly associated with root and decay of woody and herbaceous plants (Domsch et al 2007). Cylindrocarpon root rot causes losses up to 30% on ginseng (Panax quinquefolium) (Seifert et al 2003), and plays an important role in black foot rot of grapevines (Halleen et al 2004(Halleen et al , 2006, apple replant disease (Tewoldemedhin et al 2010), and beech cankers (Castlebury et al 2006), to name but a few hosts of economic importance.…”
Section: Introductionmentioning
confidence: 99%
“…To date, it has been characterised by morphology, DNA sequencing and pathogenicity assays as a pathogen of grapevine and other hosts in many countries, including Spain, Turkey, Canada, Brazil, and Italy (Martin et al 2011;Erper et al 2013;Úrbez-Torres et al 2014;dos Santos et al 2014;Aiello et al 2014 In other countries, researchers have studied the pathogenicity of D. pauciseptata isolates recovered from woody plants of grapevines and other hosts. In South Africa, four species ("C. " destructans, I. liriodendri, D. macrodidyma, D. pauciseptata) recovered from apple roots were able to induce lesion development on seedling roots with variable pathogenicity, except for one isolate of D. pauciseptata (STE-U6630), which did not cause a significant amount of root rot or reduction of weight and height (Tewoldemedhin et al 2011). In Turkey, Erper et al (2013) tested the pathogenicity of selected isolates from a group identified as Dactylonectria and Ilyonectria species, including a D. pauciseptata isolate from kiwifruit.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important in apple [7], pine and other conifer seedlings, and the forest nurseries [8,9]. Neonectria macrodidyma is a necrotic plant pathogen and a new name was recently proposed as Dactylonectria macrodidyma (syn.…”
Section: Introductionmentioning
confidence: 99%